1970
DOI: 10.4314/mmj.v27i4.2
|View full text |Cite
|
Sign up to set email alerts
|

Late-stage disease at presentation to an HIV clinic in eastern Tanzania: A retrospective cross-sectional study

Abstract: Background Late presentation and delayed treatment initiation is associated with poor outcomes in patients with HIV. Little is known about the stage at which HIV patients present at HIV clinics in Tanzania.Aim: This study aimed at determining the proportion of HIV patients presenting with WHO clinical stages 3 and 4 disease, and the level of immunity at the time of enrollment at the care and treatment center.Methods A retrospective cross-sectional study was conducted among 366 HIVinfected adults attending HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The prevalence of LHD in the index study is similar to a prevalence rate of 61% reported in 2012 from Mexico (Crabtree-Ramirez et al, 2012). A lower prevalence rate of 40% was reported from a recent study done in eastern Tanzania (Mhozya et al, 2015). The difference in prevalence of LHD could partly be explained by the difference in study setting.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The prevalence of LHD in the index study is similar to a prevalence rate of 61% reported in 2012 from Mexico (Crabtree-Ramirez et al, 2012). A lower prevalence rate of 40% was reported from a recent study done in eastern Tanzania (Mhozya et al, 2015). The difference in prevalence of LHD could partly be explained by the difference in study setting.…”
Section: Discussionsupporting
confidence: 82%
“…The CD4 counts were stratified into 2 with a cut-off point of 200cells/µl. Accordingly patients with CD4 counts <200cells/µl on diagnosis were coded as having Late HIV diagnosis as used in other studies (Crabtree-Ramirez et al, 2012;Beyene & Beyene 2015;Mhozya, 2015). Continuous variables were expressed as means with interquartile range and categorical data were expressed as frequencies and percentages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study by Bancos et 10,12,13 and evaluation of adrenal function among critically ill HIV/ AIDS patients is complex. These recent studies suggest decreased cortisol breakdown among critically ill patients as the main contributing factor to elevated cortisol levels and there is need for a well-designed and large sample size research to explore early diagnosis, optimal evaluation and treatment of adrenal insufficiency in critically ill patients.…”
Section: Discussionmentioning
confidence: 99%
“…11 In patients with HIV/AIDS, AI is one of the common endocrine manifestation and in developing countries, almost half of these newly diagnosed HIV and hospitalized HIV patient with advanced disease have AI and majority of these patients also have TB/HIV coinfection. 12 With almost 50% prevalence of adrenal insufficiency in patients with advanced HIV disease, it is worrisome that adrenal insufficiency diagnosis and evaluation is neglected in these patients that poses a major contributing factors in morbidity and mortality in this population. [11][12][13]…”
Section: Discussionmentioning
confidence: 99%